Peran Budaya Organisasi dalam Meningkatkan Kinerja Karyawan Non-Medis di Rumah Sakit Swasta - Nahda Qonita Diniya (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
This study examines the role of organizational culture and supervision systems in improving the performance of non-medical staff in private hospitals. Using a quantitative approach with 85 respondents, the analysis shows a positive and significant relationship between organizational culture and non-medical staff performance. The most influential dimensions are teamwork, results orientation, and employee involvement. These findings highlight that strengthening organizational culture and continuous supervision are essential to achieving organizational goals and enhancing the quality of non-medical services.